Urgensi Nilai-nilai Esoteris pada Kitab Al-Munqidz min ad-Dhalal Karya Imam Al-Ghazali terhadap Pendidikan Islam dalam Mempersiapkan Generasi Indonesia Emas 2045 - Muhamad Karyawan; Priyanggo Karunia Rahman (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Toward Indonesia Gold 2045, national development emphasizes the importance of strengthening human resources that are excellent and globally competitive. However, material progress without spiritual balance may lead to moral crisis and value disorientation. In this context, Islamic esoteric values serve as a vital foundation for Islamic education that focuses on character formation and spirituality. This study aims to examine the urgency of esoteric values in Imam al-Ghazali’s Al-Munqidz min ad-Dhalāl and their relevance to Islamic education in preparing Indonesia’s Golden Generation 2045. The research employed a qualitative approach through library research with hermeneutic-thematic analysis of classical texts and supporting literature. The findings reveal three key esoteric values emphasized by al-Ghazali: mujāhadah (spiritual perseverance), muḥāsabah (self-introspection), and uzlah (self-restraint and inner tranquility). These values are highly relevant to character education through the integration of affective, reflective, and contemplative dimensions in Islamic learning. The study concludes that strengthening al-Ghazali’s esoteric values can serve as a conceptual framework for developing a holistic Islamic education curriculum that fosters knowledgeable, ethical, and spiritually grounded generations toward Indonesia Gold 2045